An Analysis of Factors Responsible for High Out of School Children in Nigeria and Way Forward - Niyi Jacob Ogunode; Chinwuba Mary Adanna (Researchparks Publishing, 2022)
One of the major problem facing Nigeria as Country is how to address the problem of out of school children. Every year the population of out of school children keeps increasing. It has been observed that Nigeria has the highest out of school children in the World. This paper examined the factors responsible for out of school children in Nigeria. Among other things, the paper discussed are; concept of out of school children, factors responsible for out of school children in Nigeria and the paper suggested the way forward.